The Influence Of Occupational Safety And Health (K3) On Employee Work Productivity With Multiple Linear Regression Methods At Pt. Udm - Novia Catur Iswanto; Soerahman; Abu Naim; Rahmat Saputra (GoAcademica Research & Publishing, 2023)
The goal of this study was to see how Occupational Safety and Health affected employee productivity. This type of study is quantitative research. In this study, 50 people were polled using a questionnaire technique. Techniques for data analysis that include multiple linear regression analysis, a partial test (t-test), and a simultaneous test (F-test). SPSS 25.0 is used in the computation method. According to the test results, occupational safety and health have a favorable and considerable impact on staff productivity at PT UDM. Occupational health and safety are important factors that influence employee work productivity. The results showed that the occupational health variable (X1) has the most significant influence on employee productivity (Y), according to the equation Y = 10.246 + 0.679X1 + 0.442X2+C. This is demonstrated by the highest multiple linear regression value of 10.246 with a significant value of 0.02 when compared to the work safety variable, which has a coefficient value of 0.679 with a significant value of 0.001. In other words, the occupational health program is the most important component in improving the work productivity of PT UDM employees.